2021
DOI: 10.1111/cbdd.13978
|View full text |Cite
|
Sign up to set email alerts
|

Specific delivering of RNAi using Spike's aptamer‐functionalized lipid nanoparticles for targeting SARS‐CoV‐2: A strong anti‐Covid drug in a clinical case study

Abstract: Coronavirus (SARS‐CoV‐2) as a global pandemic has attracted the attention of many scientific centers to find the right treatment. We expressed and purified the recombinant receptor‐binding domain (RBD) of the SARS‐CoV‐2 spike (S) protein, and specific RBD aptamers were designed using SELEX method. RNAi targeting nucleocapsid phosphoprotein was synthesized and human lung cells were inoculated with aptamer‐functionalized lipid nanoparticles (LNPs) containing RNAi. The results demonstrated that RBD aptamer having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 40 publications
(45 reference statements)
0
38
0
Order By: Relevance
“…Structure proteins are needed for virion assembly, and it has been shown that in particular the spike protein is under high selection pressure, resulting in high numbers of mutations ( Weisblum et al, 2020 ; Callaway, 2021 ; He et al, 2021 ; Chen et al, 2022 ). However, an approach based on siRNA targeting the N-protein gene of SARS-CoV-2 (complexed with lipid nanoparticles that coupled to ACE2 binding aptamers) has been described by Saify Nabiabad et al (2022) . Since aptamers were used in this study having an inhibitory effect on viral infection solely by blocking the binding of SARS-CoV-2 spike protein to ACE2, the proportion of efficacy of the siRNA in vivo is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Structure proteins are needed for virion assembly, and it has been shown that in particular the spike protein is under high selection pressure, resulting in high numbers of mutations ( Weisblum et al, 2020 ; Callaway, 2021 ; He et al, 2021 ; Chen et al, 2022 ). However, an approach based on siRNA targeting the N-protein gene of SARS-CoV-2 (complexed with lipid nanoparticles that coupled to ACE2 binding aptamers) has been described by Saify Nabiabad et al (2022) . Since aptamers were used in this study having an inhibitory effect on viral infection solely by blocking the binding of SARS-CoV-2 spike protein to ACE2, the proportion of efficacy of the siRNA in vivo is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, RNAi is a promising therapeutic approach to fight infections caused by pathogenic viruses featuring single-stranded RNA genomes and subgenomic RNA transcripts (e.g., hepatitis C virus, respiratory syncytial virus, influenza, coronaviruses) [13][14][15][16]. The worldwide rampant severe acute respiratory syndrome coronavirus 2 pandemic has especially catalyzed the progress in promising antiviral siRNA therapy development [17][18][19][20][21].…”
Section: The Challenge: Developing the Optimal Sirnamentioning
confidence: 99%
“…in China in 2020 where the receptor‐binding domain (RBD) of the S protein from the wildtype SARS‐CoV‐2 was used as the target [42] . RBD was also used as the target for aptamer selection in four other studies [44,51–53] . The S1 subdomain and full trimeric S proteins have also been used as targets for SELEX, as reported by three and two groups, respectively [43,45,47,48,50] .…”
Section: Aptamers For the S Protein Of Sars‐cov‐2mentioning
confidence: 99%
“…We note that a ∼40‐nucleotide random region has been widely used in previous SELEX studies, [15] and thus it is not surprising that most of the S protein aptamer selections adopted this size. The study by Saify Nabiabad used a random domain of only 22 nucleotides [52] . Although this size of random domain is less common, small‐sized aptamers do exist.…”
Section: Aptamers For the S Protein Of Sars‐cov‐2mentioning
confidence: 99%